Effects of Salt Stress on the Biochemical Characteristics of the Aquatic Plant Lemna minor L. (1753). - Hzaa, Ahmed Y.L.; Hashim , Mahmood Sh.; Al-Waeli, Aqeel A.A; Al-Maliky, Tariq H.Y. (Mesopotamian Journal of Marine Sciences, 2025)
One of the most essential abiotic elements that has an important influence on plant development, growth, and yield is salinity. The current study revealed how the biochemical characteristics of Lemna minor L. plant were impacted by different levels of sodium chloride (0, 50, 100, 125, 150, 175, and 200 mM).The experiment was carried out in March and April of 2024. The measured amount of chlorophyll an at 50 mM was certainly greater when compared with that of the control treatment, achieving 1.0464 mg/g. At the same time, the percentages of chlorophyll a, b, and total at the other concentrations were lesser than that of the control. The results showed a rise in proline levels that related to elevated salt concentrations, with the peak proline level measured at 0.573 mg/g at a concentration of 200 mM, reflecting a 309 percent increase relative to the control treatment. The analysis of minerals revealed changes in nutrient levels. The largest rise in zinc level, 0.8993 mg/g, was measured at 125 mM, which implies a 23.2% increase. Boron levels were elevated at 200 mM, reaching 0.8550 mg/g. Manganese levels lowered considerably at raised salt concentrations, with the highest concentration, 0.1987 mg/g detected at 50 mM. Copper levels showed considerable fluctuations, reaching a high of 0.0194 mg/g at 200 mM and a low of 0.0121 mg/g at 175 mM. Iron levels increased at a concentration of 125 millimolar, reaching 1.4966 mg/g, a 339% increase compared to the control treatment. Calcium levels also increased with increasing salinity concentrations, with the highest level recorded at 1.6815 mg/g at a concentration of 150 mM. Magnesium levels showed an increase with reducing salinity concentrations, with the highest concentration at 50 mM reaching 1.0032 mg/g. The results above indicate that Limna minor L. promotes osmotic adaptation and selective mineral management to cope with salt stress. The study aims to assess the ability of duckweed (Limna minor L.) to grow and reproduce under different levels of salinity, in order to determine the extent to which it can be utilized as an economical feed source for animals in salinity-affected environments.